2005
DOI: 10.1158/0008-5472.can-03-3580
|View full text |Cite
|
Sign up to set email alerts
|

Ron Receptor Signaling Augments Mammary Tumor Formation and Metastasis in a Murine Model of Breast Cancer

Abstract: The tyrosine kinase receptor Ron has been implicated in several types of cancer, including overexpression in human breast cancer. This is the first report describing the effect of Ron signaling on tumorigenesis and metastasis in a mouse model of breast cancer. Mice with a targeted deletion of the Ron tyrosine kinase signaling domain (TKÀ/À) were crossed to mice expressing the polyoma virus middle T antigen (pMT) under the control of the mouse mammary tumor virus promoter. Both pMT-expressing wild-type control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 41 publications
4
72
1
Order By: Relevance
“…It has been shown that mammary-specific Ron overexpression induces highly metastatic mammary tumors in mice (34) and that Ron signaling augments mammary tumor formation and metastasis in a murine model of breast cancer (35). Metastasis is a complex, multistep process that requires a tumor cell to fulfill two rate-limiting steps: invasion and distant colony formation (36 -38).…”
mentioning
confidence: 99%
“…It has been shown that mammary-specific Ron overexpression induces highly metastatic mammary tumors in mice (34) and that Ron signaling augments mammary tumor formation and metastasis in a murine model of breast cancer (35). Metastasis is a complex, multistep process that requires a tumor cell to fulfill two rate-limiting steps: invasion and distant colony formation (36 -38).…”
mentioning
confidence: 99%
“…RON modulates diverse processes involved in tumor progression and metastasis in a variety of human cancers (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Consequently, an understanding of the molecular alterations of RON that facilitate tumor progression and metastasis will provide insight into approaches to optimized target therapies.…”
Section: Discussionmentioning
confidence: 99%
“…RON is a heterodimeric protein of disulfide-linked extracellular α and transmembrane β subunits with intrinsic tyrosine kinase activity derived from proteolytic cleavage of a single-chain precursor of 170 kDa (13)(14)(15)(16)(17)(18)(19). Transgenic mouse models overexpressing RON in lung or mammary epithelial cells develop lung and breast carcinomas and are associated with metastatic dissemination (20,21). RON is overexpressed in a variety of human epithelial cancers including breast, colon, lung, ovary, pancreas and bladder (22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The currently available evidence to support the potential role of RON in carcinogenesis of pancreatic cancer and implications for future targeted therapy in treating pancreatic cancer was previously reviewed (11). RON has been demonstrated to serve important roles in pancreatic cancer carcinogenesis (12)(13)(14), epithelial-mesenchymal transition (15,16), tumor migration (17)(18)(19), angiogenesis (20,21), cancer stem cells (22) and apoptotic resistance (14,23,24) as a part of the progression of pancreatic cancer, suggesting that RON may be a potential therapeutic target in the treatment of pancreatic cancer. In particular, RON signaling was previously identified to increase VEGF level and promote microtubule formation in BxPC-3 and FG cells, suggesting an specific mechanism for the association of RON with pancreatic cancer progression (21).…”
Section: Introductionmentioning
confidence: 99%